Oncologists' attitudes and practices regarding fertility preservation at a tertiary academic center. Issue 28 (1st October 2022) - Ragavan, Meera Vimala; Kennedy, Vanessa Elaine; Banerjee, Rahul; Lin, Amy M.; Velazquez Manana, Ana I.
Abstract : 190 Background: Infertility is a significant long-term consequence of cancer treatment and can negatively impact health related quality of life. As the incidence of cancer rises in younger populations and an increasing number of patients are prescribed systemic therapy in the neoadjuvant and adjuvant settings, the proportion of patients at risk for infertility will rise in tandem. Referrals for fertility preservation (FP), however, are low nationally and at our institution. Our study aimed to characterize oncologist attitudes and practices around FP and identify barriers to FP in patients with cancer. Methods: We developed a 21-item anonymous survey informed by literature review and input from FP stakeholders. The survey was distributed electronically to all faculty and fellows (n = 103) within our division of hematology/oncology during a division-wide conference on FP and subsequently emailed to all faculty and fellows, with three weekly follow up reminder emails. Results: 41 respondents completed the survey (response rate 40%), including faculty (46%) and fellows (39%). Respondents were predominantly male (49%), aged 25-40 (51%), white (44%), and non-Hispanic (73%). Most respondents agreed that FP should be offered to all patients with cancer receiving cytotoxic therapy (95%), however fewer respondents agreed that FP should be offered if it would cause a treatment delay by 2 weeks or more (63%). Respondents felt more comfortable counseling male patients (65%) than female patients (54%) and a larger proportion (41%) knew how to make referrals for sperm preservation (compared to 22% for oocyte preservation). The top barriers to counseling were patient past childbearing age (41%), provider did not remember to discuss (37%), and need for urgent treatment initiation (32%). The top barriers for an interested patient to undergo FP were perceived cost by patient (61%), need for urgent treatment initiation (59%), and patient was too overwhelmed to proceed with FP (42%). Conclusions: Oncologists agreed that FP is an important part of cancer care. However, many stated that cancer treatment initiation was often too time sensitive to counsel patients regarding fertility risks and make FP referrals. The FP referral process was not clear to many respondents. Clinic-level interventions are warranted to ensure timely patient access to FP. Based on the results of this study, we will launch a fellow-led Plan-Do-Study-Act Quality Improvement intervention to increase FP referrals in our clinics.